A new granite cave dwelling endemic species of the Cyrtodactylus intermedius group (Squamata: Gekkonidae) from Hon Son Island, Kien Giang Province, Vietnam - Tran, Thinh Gia; Lam, Ngon Quang; Nguyen, Truong Minh Nhat; Nguyen, Nga Thi; Nguyen, Thao Thi Phuong; Smith, Jacob; Nguyen, Vu Dang Hoang; Grismer, L Lee (Zootaxa, 2024)
During field work on Hon Son Island, we discovered a new species of the genus Cyrtodactylus inferred from genetic and morphological evidence. Phylogenetic analyses based on the mitochondrial gene ND2, delimit Cyrtodactylus borgattaorum sp. nov. as a new species in the C. intermedius group and the strongly supported sister species of C. phuquocensis in both Bayesian inference and Maximum Likelihood analyses. The new species is distinguished from all other members of the intermedius group by having the combination of 12 supralabials; 10 or 11 infralabials; 22 or 23 small, rounded, smooth, paravertebral tubercles; 12 rows of small, rounded, smooth, longitudinally arranged body tubercles; 35–39 ventrals; 8–10 expanded subdigital lamellae, 12 or 13 unexpanded subdigital lamellae, and 21 or 22 total subdigital lamellae on the fourth toe; 21 or 22 enlarged femorals; 8 or 9 enlarged precloacals; 8 or 9 precloacal pores in males; three rows of enlarged post-precloacals; postcloacal tubercles; enlarged femorals and enlarged precloacals not continuous; proximal femorals nearly same size of distal femorals; body tubercles smooth, greatly reduced; no pocketing between digits on the hands and feet; two dark-colored pigmented blotches on top of head; four dark-colored dorsal bands lacking lightened centers, thinner than light-colored interspaces between bands, bordered by prominent white tubercles; no dark body markings in light-colored interspaces between bands; limbs bearing white tubercles; and six dark-colored and light-colored caudal bands. Cyrtodactylus borgattaorum sp. nov. lives in syntopy with Cyrtodactylus eisenmanae which is the first record of syntopy between granite cave dwelling Cyrtodactylus.